Wide Distribution and Specific Resistance Pattern to Third-Generation Cephalosporins of Enterobacter cloacae Complex Members in Humans and in the Environment in Guadeloupe (French West Indies) - Pot, Matthieu; Reynaud, Yann; Couvin, David; Ducat, Célia; Ferdinand, Séverine; Gravey, François; Gruel, Gaëlle; Guérin, François; Malpote, Edith; Breurec, Sébastien; Talarmin, Antoine; Guyomard-Rabenirina, Stéphanie (Frontiers in Microbiology, 2021)
Species belonging to Enterobacter cloacae complex have been isolated in numerous environments and samples of various origins. They are also involved in opportunistic infections in plants, animals, and humans. Previous prospection in Guadeloupe (French West Indies) indicated a high frequency of E. cloacae complex strains resistant to third-generation cephalosporins in a local lizard population (Anolis marmoratus), but knowledge of the distribution and resistance of these strains in humans and the environment is limited. The aim of this study was to compare the distribution and antibiotic susceptibility pattern of E. cloacae complex members from different sources in a “one health” approach and to find possible explanations for the high level of resistance in non-human samples. E. cloacae complex strains were collected between January 2017 and the end of 2018 from anoles, farm animals, local fresh produce, water, and clinical human samples. Isolates were characterized by the heat-shock protein 60 gene-fragment typing method, and whole-genome sequencing was conducted on the most frequent clusters (i.e. C-VI and C-VIII). The prevalence of resistance to third-generation cephalosporins was relatively high (56/346, 16.2%) in non-human samples. The associated resistance mechanism was related to an AmpC overproduction; however, in human samples, most of the resistant strains (40/62) produced an extended-spectrum beta-lactamase. No relation was found between resistance in isolates from wild anoles (35/168) and human activities. Specific core-genome phylogenetic analysis highlighted an important diversity in this bacterial population and no wide circulation among the different compartments. In our setting, the mutations responsible for resistance to third-generation cephalosporins, especially in ampD, were diverse and not compartment specific. In conclusion, high levels of resistance in non-human E. cloacae complex isolates are probably due to environmental factors that favor the selection of these resistant strains, and this will be explored further.